Wild Race by Teenagers in Padang City in the Aspect of Criminology - Putra Pratama, Bisma; Sembiring, Susanti; Febrina, Yuka (Greenation International Journal of Law and Social Sciences, 2023)
The purpose of this study was to find out the factors that led to wild races by teenagers in the city of Padang and the efforts made by the police in dealing with cases of wild racing . The approach used in this study is a normative juridical approach as the main approach, supported by an empirical juridical approach. Based on the results of the research and discussion, it was obtained : the factors for the occurrence of illegal races by teenagers in the city of Padang, are due to bad associations of teenagers, lack of attention from parents, lack of racing facilities for teenagers. Illegal racing disrupts smooth running, is troubling, and endangers both. The efforts made by the Padang Police in dealing with cases of wild racing by teenagers in the city of Padang include preventive measures : 1) conduct socialization in schools, campuses (especially to students ), crossroads, patrolling ; 2) condition creation operation. The repressive effort carried out by the Padang Police is by issuing a ticket (proof of violation) for 3 months.